Normal and sonographic anatomy of selected peripheral nerves. Part I: Sonohistology and general principles of examination, following the example of the median nerve - Berta Kowalska; Iwona Sudoł-Szopińska (Journal of Ultrasonography, 2012)
Ultrasonography is an established method for imaging peripheral nerves. It serves to supplement the physical examination, electromyography, and magnetic resonance imaging. It enables the identification of post-traumatic changes of nerves, neuropathies secondary to compression syndromes, inflammatory or neoplastic nerve lesions as well as the evaluation of postoperative complications. In certain situations, this technique is the imaging method of choice. It is increasingly used in anesthesiology for regional anesthesia. As in the case of other ultrasound imaging studies, the examination of peripheral nerves is non-invasive, well-tolerated by patients, and relatively inexpensive. This article presents the histological structure of peripheral nerves and their appearance in ultrasonography. It also presents the examination technique, following the example of the median nerve, and includes a series of diagrams and ultrasound images. The interpretation of the shape, echogenicity, thickness and vascularity of nerves is described, as well as their relation to the surrounding tissues. The “elevator technique”, which consists of locating a set nerve at a characteristic anatomic point, and following it proximally or distally, has been explained. The undisputed benefits of the ultrasound examination have been presented, including its advantages over other diagnostic methods. These advantages include the dynamic component of the ultrasound examination and the possibility of correlating the patient’s symptoms with the ultrasound images. As an example, the proper anatomy and the ultrasonographic appearance of the median nerve were described. This nerve’s course is presented, its divisions, and characteristic reference points, so as to facilitate its location and identification, and enable subsequent use of the aforementioned “elevator technique”. This article opens a series of publications concerning anatomy, technique of examination and pathologies of peripheral nerves.